John Bowlby and attachment theory - Holmes, Jeremy, 1943-; ProQuest (firma) (London : Routledge, Taylor & Francis Group, 2014)
John Bowlby is one of the outstanding psychological theorists of the twentieth century. This new edition of John Bowlby and Attachment Theory is both a biographical account of Bowlby and his ideas and an up-to-date introduction to contemporary attachment theory and research, now a dominant force in psychology, counselling, psychotherapy and child development. Jeremy Holmes traces the evolution of Bowlby's work from a focus on delinquency, material deprivation and his dissatisfaction with psychoanalysis's imperviousness to empirical science to the emergence of attachment theory as a psychological model in its own right. This new edition traces the explosion of interest, research and new theories generated by Bowlby's followers, including Mary Main's discovery of Disorganised Attachment and development of the Adult Attachment Interview, Mikulincer and Shaver's explorations of attachment in adults and the key contributions of Fonagy, Bateman and Target. The book also examines advances in the biology and neuroscience of attachment. Thoroughly accessible yet academically rigorous, and written by a leading figure in the field, John Bowlby and Attachment Theory is still the perfect introduction to attachment for students of psychology, psychiatry, counselling, social work and nursing.
I. Origins -- II. Attachment theory -- III. Implications
Obsahuje bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: Bowlby, John, -- 1907-1990; 20. století; psychoanalytici -- Velká Británie -- 20. století; teorie attachmentu; psychoanalysts -- Great Britain -- 20th century; attachment theory; monografie; e-knihy online; monographs; e-books online